Aramid-based solid polymer electrolyte membrane with hydrogen bond defect and preparation method and application thereof
By grafting the ether segment at the NH site of the aramid material, partial hydrogen bonding is destroyed, the problems of difficult dissolution of aramid material and poor compatibility with alkali metal salts are solved, and a polymer electrolyte membrane with high conductivity and mechanical strength are achieved, with good practical properties.
Patent Information
- Application Number
- CN202411971660.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The existing polymer electrolyte materials have low conductivity at room temperature and insufficient mechanical properties, making it difficult to meet practical needs. Moreover, aramid materials have a very strict molecular structure and strong interaction between hydrogen bonds, and are difficult to dissolve, and lack compatibility with alkali metal salts.
The ether segment is grafted at the NH site of aramid by chemically grafting part of hydrogen bonds, improving solubility and increasing compatibility with alkali metal salts, providing ion-transported complexing sites, and forming an aramid-based solid polymer electrolyte membrane with hydrogen bond defects.
It improves the solubility and film formation of aramid materials, enhances the transmission ability of alkali metal ions, achieves a balance of high ionic conductivity and mechanical strength, and has good chemical and electrochemical stability.
Smart Images

Figure CN119725715A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material chemistry, and in particular to an aramid-based solid polymer electrolyte membrane with hydrogen bond defects, and a preparation method and application thereof. Background Art
[0002] Solid electrolytes are the key technology for the next generation of energy storage batteries. Polymer electrolytes have good flexibility, are conducive to forming a good interface contact between the electrode and the electrolyte, can withstand the volume deformation of the electrode material during the charge and discharge process, are light in weight, easy to process, and suitable for large-scale production, making them a strong candidate material for solid electrolytes. The development of polymer electrolytes originated from the PEO system reported by Wright et al. in the 1970s, which has good film-forming properties. However, the conductivity of polymer systems based on PEO and its derivatives at room temperature still does not meet the practical requirements, and requires sufficient segment movement under higher temperature conditions. In addition, the glass transition temperature of the polyether segment is low, and the mechanical properties are difficult to meet the practical needs. In recent years, researchers have tried to develop other systems, such as polycarbonate, polyacrylate, acrylonitrile, polyvinylidene fluoride and other systems. The introduction of polar groups enhances the dissociation of alkali metal salts to a certain extent, but often has obvious shortcomings in film-forming properties, dimensional stability, and segment dynamics. Therefore, the development of polymer electrolyte materials with good alkali metal ion transport properties, high mechanical strength, good film-forming properties, and chemical stability has great practical and economic value.
[0003] Aramid (commonly known as Kevlar) is a polymer material with excellent comprehensive performance. It has the characteristics of high strength, light weight, high temperature resistance (decomposition temperature>560℃), friction resistance, insulation, flame retardancy, chemical stability and corrosion resistance. It is widely used in military, aerospace and electrical fields, and has great application prospects in the field of batteries. At present, the application of aramid materials in batteries is mainly concentrated in the diaphragm, used as a diaphragm or diaphragm coating (for example, patents CN103343423B, CN109860483B, CN101356665A, CN202310626699.1). Tesla's high-end Model S series has been equipped with batteries using aramid coated diaphragms, which can significantly improve the thermal safety performance of the battery. Although the use of diaphragms or diaphragm coatings can improve battery safety to a certain extent, the use of a large amount of electrolyte in the overall assembly cannot be avoided, and the use of coatings is also likely to increase production costs.
[0004] Using aramid as the matrix of polymer electrolyte can truly replace the poorly thermally stable polyolefin (PP, PE, etc.) separators used in traditional batteries, reducing manufacturing costs while improving energy density and safety. Despite its many potential advantages, the application of aramid materials as polymer electrolytes to replace separators has not been realized due to its regular molecular structure, strong hydrogen bond interactions, difficulty in dissolving, and lack of technical means to mix with alkali metal salts. Summary of the invention
[0005] In order to solve the above problems, the present invention provides an aramid-based solid polymer electrolyte membrane with hydrogen bond defects. By chemically grafting ether segments at the NH sites of aramid, the dissolution problem of aramid is improved by destroying some hydrogen bonds, and at the same time, its compatibility with alkali metal salts is increased, providing complexation sites for ion transmission, and can be used as an alkali metal ion conductor to achieve stable battery circulation. From the perspective of molecular structure, aramid is a linear macromolecule formed by interconnecting amide groups (CO-NH) and benzene rings. The structural stability comes from the hydrogen bonds between the amide groups and the π-π stacking of the benzene rings, which can provide the high size and thermal stability required by the polymer electrolyte. Unlike aromatic polyamides such as polyimide (tertiary amine), aramid not only coordinates with alkali metal cations through carbonyl groups (C=O), but also Lewis-acidic secondary amine hydrogen (-NH-) can form hydrogen bonds with salt anions. This typical hydrogen bond defective polymer electrolyte system is conducive to further compensating the lattice energy of salt dissociation, improving the degree of charge separation, and obtaining faster ion migration kinetics.
[0006] The first aspect of the present invention provides an aramid-based solid polymer electrolyte membrane with hydrogen bond defects, the aramid-based solid polymer electrolyte membrane comprising a chemically modified ether segment grafted aramid matrix with hydrogen bond defects and an anhydrous alkali metal salt;
[0007] The chemically modified ether chain segment grafted aramid matrix is obtained by grafting ether chains on the para- or meta-aramid NH sites to destroy some hydrogen bonds.
[0008] Furthermore, the polymer electrolytes currently prepared based on conventional para- or meta-aramid fibers are far from meeting the use requirements in terms of process and ion transmission capacity, and have defects such as difficulty in dissolving and lack of ion transmission sites. This application uses a chemical method to graft ether chains on the NH sites of aramid fibers, and introduces ether side chains on aramid fibers to destroy some of the original strong hydrogen bond structures and local hydrogen bond defects. On the one hand, it increases solubility and improves the film-forming process, and is also conducive to the entry of alkali metal salts into the amide group to form room temperature molten salts with it; on the other hand, the introduced ether segments can be used as ion transmission sites, enhancing the overall ion transmission capacity.
[0009] The structural formula of the chemically modified ether segment grafted aramid is shown below:
[0010]
[0011] Wherein, in Formula 1 and Formula 2, m represents the number of aramid units grafted with ether segments, n represents the number of ungrafted aramid units, and m+n represents the total number of units of the aramid structure, i.e., the chain length of the aramid. Optionally, m+n is selected from an integer of 10-10000 and satisfies 0.2≤m / (m+n)≤1; r represents a random copolymer; R1 represents a phenylene group. or m-phenyl x represents the number of ether segment units, and x is selected from an integer of 1-5; R2 is -C y H 2y+1 or -C y H z F 2y+1-z , y is an integer selected from 1-4, and z is an integer satisfying 0≤z≤2y+1. In order to further ensure the film-forming property, solubility and dissociation property of the ether segment grafted aramid to the metal salt, m is preferably 0.4≤m / (m+n)≤0.75, x is preferably 2, and y is preferably 1.
[0012] Optionally, by mass fraction, the chemically modified ether segment grafted aramid matrix is 5%-92%, and the anhydrous alkali metal salt is 8%-95%. Further considering the influence of the ether segment grafted aramid on the film forming and mechanical properties of the electrolyte membrane and the carrier concentration, preferably, the ether segment grafted aramid is 20%-40%, and the anhydrous alkali metal salt is 60%-80%.
[0013] Optionally, the preparation method of chemically modified ether segment grafted aramid fiber comprises the following steps:
[0014] S1: dissolving a certain amount of aramid and halogenated ether monomer in a polar solvent, adding an acid binding agent, and reacting at a temperature of 50-80°C to obtain an intermediate product;
[0015] S2: adding a precipitant to the intermediate product obtained in step S1 to react, and then washing and drying in sequence to obtain chemically modified ether segment grafted aramid.
[0016] Optionally, the halogenated ether is one of chloroether, bromoether or iodoether;
[0017] Optionally, the aramid is one of poly(p-phenylene terephthalamide) (referred to as p-aramid) or poly(m-phenylene isophthalamide) (referred to as m-aramid);
[0018] Optionally, the acid binding agent is one or more of potassium hydroxide, sodium hydroxide, potassium carbonate or sodium hydride;
[0019] Optionally, the precipitant is one or more of water, hydrochloric acid solution, methanol, ethanol, and sodium chloride solution;
[0020] Optionally, the polar solvent is one or more of N,N-dimethylformamide (DMF for short), N,N-dimethylacetamide, dimethyl sulfoxide (DMSO for short), and N-methylpyrrolidone (NMP for short);
[0021] Optionally, the anhydrous alkali metal salt is a lithium salt, a sodium salt or a potassium salt.
[0022] Optionally, the lithium salt can be one or more of lithium fluoride (LiF), lithium chloride (LiCl), lithium bromide (LiBr), lithium iodide (LiI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoroacetate (CF3COOLi), lithium trifluoromethanesulfonate (CF3SO3Li), lithium bis(trifluoromethanesulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(pentafluoroethanesulfonyl)imide (LiPFTFSI), lithium bis(trifluorooxalatoborate) (LiDFOB), lithium tetrachloroaluminate (LiAlCl4), and polymer lithium salts.
[0023] Optionally, the polymer lithium salt may be a carboxylic acid-based polyanion lithium salt, a sulfonic acid-based polyanion lithium salt, a boron-based polyanion lithium salt, an aluminum-silicon-based polyanion lithium salt or a trifluoromethylsulfonyl imide-based polyanion lithium salt.
[0024] Optionally, the sodium salt can be one or more of sodium fluoride (NaF), sodium chloride (NaCl), sodium bromide (NaBr), sodium iodide (NaI), sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium trifluoroacetate (CF3COONa), sodium trifluoromethanesulfonate (CF3SO3Na), sodium bis(trifluoromethanesulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium bis(pentafluoroethanesulfonyl)imide (NaPFTFSI), sodium bis(fluorooxalatoborate) (NaDFOB), sodium tetrachloroaluminate (NaAlCl4), and polymer sodium salt.
[0025] Optionally, the polymer sodium salt may be a carboxylate-based polyanion sodium salt, a sulfonic acid-based polyanion sodium salt, a boron-based polyanion sodium salt, an aluminum-silicon-based polyanion sodium salt or a trifluoromethylsulfonyl imide-based polyanion sodium salt.
[0026] Optionally, the potassium salt is specifically one or more of potassium fluoride (KF), potassium chloride (KCl), potassium bromide (KBr), potassium iodide (KI), potassium hexafluorophosphate (KPF6), potassium tetrafluoroborate (KBF4), potassium perchlorate (KClO4), potassium hexafluoroarsenate (KAsF6), potassium trifluoroacetate (CF3COOK), potassium trifluoromethanesulfonate (CF3SO3K), potassium bis(trifluoromethanesulfonyl)imide (KFSI) or potassium bis(trifluoromethanesulfonyl)imide (KTFSI), potassium bis(pentafluoroethanesulfonyl)imide (KPFTFSI), potassium bis(fluorooxalatoborate) (KDFOB), potassium tetrachloroaluminate (KAlCl4), and polymer potassium salts.
[0027] Alternatively, the polymer potassium salt may be a carboxylate-based polyanion potassium salt, a sulfonate-based polyanion potassium salt, a boron-based polyanion potassium salt, an aluminum-silicon-based polyanion potassium salt or a trifluoromethylsulfonyl imide-based polyanion potassium salt.
[0028] Optionally, the aramid-based solid polymer electrolyte membrane with hydrogen bond defects also includes an ion conduction auxiliary agent, which is a small molecule ion transport agent and / or fillers such as oxides, sulfides, halides and inorganic particles or salts thereof. By introducing an appropriate amount of ion conduction auxiliary agent, the ion transport capacity of the solid electrolyte can be further improved, and a local ion transport path can be created to further improve the ion conductivity.
[0029] Optionally, by mass fraction, the small molecule ion transporter accounts for 0%-20%; the inorganic particles such as oxides, sulfides, halides, and salts account for 0%-10%. Preferably, the small molecule ion transporter accounts for 8%-15%; the inorganic particles such as oxides, sulfides, halides, and salts account for 5%-8%.
[0030] Optionally, the small molecule ion transporter can be one or more of common aprotic organic solvents. For example, the small molecule ion transporter is one or more of cyclic carbon (sulfonate) esters, chain carbon (sulfonate) esters, cyclic ethers, chain ethers, sulfones, nitriles, and phosphates.
[0031] Optionally, the small molecule ion transporter can be ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dipropyl carbonate (DPC), vinylene carbonate (VC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), 1,4-butyrolactone (γ-BL), 4-methylbutyrolactone (γ-VL), 2-acetyl-γ-butyrolactone, ethyl acetate, butyl acetate, 2-butoxyethyl acetate, ethylene glycol dimethyl ether (DME), 1,2-dimethoxypropane, 1,2-ethoxyethane, 1,3 -dioxolane, 1,4-dioxolane, dimethanol formal, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, dimethyl sulfoxide, 1,3-propane sultone, 3-fluoro-1,3-propane sultone, 1,4-butane sultone, 1,3-propene sultone, 1,4-butene sultone, methylene methanedisulfonate, methyl methanesulfonate, ethyl methanesulfonate, vinyl methanesulfonate, propene methanesulfonate, formamide, acetamide, trimethyl phosphate, triethyl phosphate, acetonitrile, succinonitrile, adiponitrile or one or more thereof, and may also be fluorine-substituted forms of the above molecules.
[0032] Optionally, inorganic particles such as oxides, sulfides, halides, and salt fillers may be silicon oxide (SiO2), titanium oxide (TiO2), aluminum oxide (Al2O3), Na3Zr2Si2PO 12 、Na3PS4、Na3SbS4、Na 11 Sn2PS 12 、Na4Sn 0.67 Si 0.33 S4, Li 3.3 La 0.56 TiO3, LiTi2(PO4)3, Li 14 Zn(GeO4), Li7La3Zr2O 12 , Li2S-P2S5, LiBH4, LiF, LiCl, LiI, LiAlCl4, Li3OCl, LiPON, Na3Zr2Si2PO 12 、Na3PS4、Na3SbS4、Na 11 Sn2PS 12 、Na4Sn 0.67 Si 0.33 One or more of S4, NaF, NaCl, NaI, NaAlCl4, KF, KI, KCl, KAlCl4, AlCl3.
[0033] A second aspect of the present invention provides a method for preparing an aramid-based solid polymer electrolyte membrane having hydrogen bond defects, the preparation method comprising the following steps:
[0034] (1) Graft the chemically modified ether chain segment of the raw material onto the aramid matrix and add the anhydrous alkali metal salt to the solvent in a certain proportion, stir at room temperature (20 - 30 °C) to form a homogeneous casting precursor solution, and let it stand for defoaming; optionally, the solvent is N,N-dimethylformamide (abbreviated as DMF).
[0035] (2) Uniformly coat the casting precursor solution onto the surface of a glass plate to form a film, first perform one-step drying at a temperature of 25 - 60 °C; then perform two-step vacuum drying at a temperature of 60 - 90 °C to obtain an aramid-based solid polymer electrolyte membrane with hydrogen bond defects.
[0036] The third aspect of the present invention provides a battery, which is one of a lithium battery, a sodium battery or a potassium battery. The battery includes an electrolyte, a negative electrode, and a positive electrode to form a sandwich structure. The aramid-based solid polymer electrolyte membrane with hydrogen bond defects as described above is included between the positive electrode and the negative electrode.
[0037] Optionally, the battery is a lithium battery, and the negative electrode can be any active material capable of reversibly storing lithium ions, including but not limited to one of metal-based alloys (lithium metal, silicon, lithium-silicon alloy) and carbon-based materials (hard carbon, soft carbon or graphite). The positive electrode includes one of a layered oxide positive electrode (for example, LiMxO2, 0 < x ≤ 1, M = Mn, Co, Ni), a spinel structure positive electrode (for example, LiMn2O4), an olivine structure positive electrode (for example, LiFePO4), a polyanion positive electrode (for example, LiMnPO4, LiCoPO4, Li3V2(PO4)3), and a sulfur positive electrode.
[0038] Optionally, the battery is a sodium battery, and the negative electrode can be any active material capable of reversibly storing sodium ions, including but not limited to one of metal-based alloys (for example, sodium metal, tin metal, silicon or sodium-tin alloy) and carbon-based materials (for example, hard carbon, soft carbon or graphite). The positive electrode includes a layered oxide positive electrode (for example, Na x MO2, 0 < x ≤ 1, M = Ti, V, Cr, Mn, Fe, Co, Ni, Cu), a polyanion (for example, NaMPO4, Na3V2(PO4)3, Na2MP2O7, M = Fe, Mn, Co), and a Prussian blue / white analogue (for example, Na x M’[M”(CN)6], 0 < x ≤ 2, M’, M” = Mn, Ni, Co, Zn, Cu, Fe, etc.).
[0039] Optionally, the battery is a potassium battery, and the negative electrode can be any active material capable of reversibly storing potassium ions, including but not limited to metal-based alloys (for example, germanium, antimony, tin, silicon, phosphorus or phosphorus-tin alloy), carbon-based materials (for example, hard carbon, soft carbon or graphite), and titanium-based materials (for example, K2Ti4O9, K2Ti8O 17) and one of conversion materials (e.g., metal oxides, metal selenides, metal sulfides). The positive electrode includes a layered compound positive electrode (e.g., K x MO2, 0 < x ≤ 1, M = V, Cr, Mn, Co, Ni), polyanions (K3V2(PO4)3, KFePO4, KVPO4F, KVOPO4, KTiP2O7, KVP2O7, KMoP2O7, KFeSO4F), Prussian blue analogs (K x M’[M”(CN)6]Z·nH2O, 0 ≤ x ≤ 2, M’, M” = Mn, Ni, Co, Zn, Cu, Fe, etc.).
[0040] The fourth aspect of the present invention provides a method for preparing a battery. The aramid-based solid polymer electrolyte membrane with hydrogen bond defects is placed between the positive and negative electrodes and laminated and assembled into a sandwich structure, and then installed in a battery case and pressed into a solid battery.
[0041] Compared with the prior art, the present invention achieves at least one of the following beneficial effects:
[0042] (1) In the aramid-based solid polymer electrolyte membrane with hydrogen bond defects of the present invention, ether chain segments are grafted onto the NH sites by chemical methods to construct local hydrogen bond defects, making the aramid substrate have better solubility, which has a great improvement effect on the film-forming process and is conducive to large-scale popularization and application.
[0043] (2) In the aramid-based solid polymer electrolyte membrane with hydrogen bond defects of the present invention, ether chain segments are introduced by chemical grafting as ordered complexation sites for cation transport, which is conducive to reducing the long-range migration energy barrier.
[0044] (3) In the aramid-based solid polymer electrolyte membrane with hydrogen bond defects of the present invention, a local molten salt environment is formed by the residual amide groups and alkali metal salts. This modified aramid material can form a typical high-concentration salt electrolyte system (the mass ratio of salt exceeds 60%, and the content of conventional electrolyte salts is generally less than 30%), which is conducive to forming an anion-assisted local alkali metal ion transport channel and enhancing the ion transport ability.
[0045] (4) The aramid-based solid polymer electrolyte membrane with hydrogen bond defects of the present invention is solid at room temperature and exhibits a high ionic conductivity of more than 10 -4 S / cm, which can meet the requirements of actual battery applications.
[0046] (4) The aramid-based solid polymer electrolyte membrane with hydrogen bond defects of the present invention has obvious thermal stability advantages and can withstand high temperatures exceeding 200°C, while traditional polyolefin separators usually shrink at >60°C, which is likely to cause battery short-circuit failure.
[0047] (5) The aramid-based solid polymer electrolyte membrane with hydrogen bond defects of the present invention has high chemical and electrochemical stability, can match a variety of positive and negative electrode materials, and at the same time reduce interfacial side reactions and leakage during battery cycles, thereby improving battery cycle stability and life.
[0048] (6) The preparation process of the aramid-based solid polymer electrolyte membrane with hydrogen bond defects of the present invention is simple, and the process can be easily expanded for large-scale production without the need for complex equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0050] Figure 1 The nuclear magnetic hydrogen spectrum of the aramid material with hydrogen bond defects of the present invention is shown;
[0051] Figure 2 An exemplary embodiment of an aramid-based solid polymer electrolyte membrane 1# having hydrogen bonding defects of the present invention is shown;
[0052] Figure 3 An exemplary embodiment of an aramid-based solid polymer electrolyte membrane 2# having hydrogen bonding defects of the present invention is shown;
[0053] Figure 4 The electrochemical impedance spectroscopy diagram of aramid-based solid polymer electrolyte membrane 1# with hydrogen bonding defects at 40°C and 80°C is shown;
[0054] Figure 5 The electrochemical impedance spectroscopy diagram of aramid-based solid polymer electrolyte membrane 2# with hydrogen bonding defects at 40°C and 80°C is shown;
[0055] Figure 6 The electrochemical impedance spectroscopy diagram of aramid-based solid polymer electrolyte membrane 3# with hydrogen bonding defects at 40°C and 80°C is shown;
[0056] Figure 7 The electrochemical impedance spectroscopy diagram of aramid-based solid polymer electrolyte membrane 4# with hydrogen bonding defects at 40°C and 80°C is shown;
[0057] Figure 8 The electrochemical impedance spectroscopy diagram of aramid-based solid polymer electrolyte membrane 5# with hydrogen bonding defects at 40°C and 80°C is shown;
[0058] Fig. 9 The electrochemical impedance spectroscopy diagram of aramid-based solid polymer electrolyte membrane 6# with hydrogen bonding defects at 40°C and 80°C is shown;
[0059] Fig.10 The electrochemical impedance spectroscopy diagram of aramid-based solid polymer electrolyte membrane 7# with hydrogen bonding defects at 40°C and 80°C is shown;
[0060] Fig.11 The voltage-capacity curve of battery 1# is shown;
[0061] Fig.12 The voltage-capacity curve of battery 2# is shown;
[0062] Fig.13 The voltage-capacity curve of battery 3# is shown;
[0063] Fig.14 The voltage-capacity curve of battery 4# is shown;
[0064] Fig.15 A voltage-capacity graph of battery #5 is shown. DETAILED DESCRIPTION
[0065] In order to more clearly illustrate the overall concept of the present invention, a detailed description is given below in an exemplary manner in conjunction with the accompanying drawings.
[0066] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0067] Example 1
[0068] Aramid-based solid polymer electrolyte membrane with hydrogen bond defects 1#
[0069] Aramid-based solid polymer electrolyte membrane 1# with hydrogen bond defects is composed of two substances, namely, a chemically modified ether segment grafted aramid matrix with hydrogen bond defects and sodium bis(fluorosulfonyl)imide (NaFSI), and is an electrolyte membrane with low salt concentration.
[0070] The preparation method of chemically modified ether segment grafted aramid with hydrogen bond defects comprises the following steps:
[0071] S1: dissolving poly(m-phenylene isophthalamide) and bromomethyl methyl ether in a polar solvent DMF, adding an acid-binding agent sodium hydride, and reacting at a temperature of 50° C. to obtain an intermediate product;
[0072] S2: adding water to the intermediate product obtained in step S1 to precipitate, and then washing and drying in sequence to obtain chemically modified ether segment grafted aramid with hydrogen bond defects, wherein the structure of the ether segment grafted aramid is as shown in Formula 2, x=1; R1 is isophthalic acid R2 is -CH3, m+n=146.
[0073] The method for preparing an aramid-based solid polymer electrolyte membrane having hydrogen bond defects comprises the following steps:
[0074] (1) adding ether segment grafted aramid and NaFSI in a mass ratio of 1:0.1 (NaFSI accounts for 9% of the total mass) into DMF solvent, stirring until fully dispersed and dissolved to form a homogeneous precursor solution, and standing to degas to form a casting film precursor solution;
[0075] (2) The casting precursor liquid is uniformly coated on the surface of the glass plate to form a film, and first evaporated and dried at a temperature of 55°C for 10 hours; then transferred to a high-temperature vacuum oven at a temperature of 90°C for baking and drying, to obtain an aramid-based solid polymer electrolyte membrane with hydrogen bond defects.
[0076] Aramid-based solid polymer electrolyte membrane with hydrogen bond defects 2#
[0077] The aramid-based solid polymer electrolyte membrane 2# with hydrogen bond defects is composed of two substances: chemically modified ether segment grafted aramid with hydrogen bond defects and high concentration of sodium bis(fluorosulfonyl)imide (NaFSI).
[0078] The preparation method of chemically modified ether segment grafted aramid with hydrogen bond defects comprises the following steps:
[0079] S1: dissolving poly(m-phenylene isophthalamide) and bromomethyl methyl ether in a polar solvent N,N-dimethylacetamide, adding an acid-binding agent, sodium hydroxide, and reacting at a temperature of 60°C to obtain an intermediate product;
[0080] S2: adding sodium chloride solution to the intermediate product obtained in step S1 for precipitation, and then washing and drying in sequence to obtain ether segment grafted aramid, wherein the structure of the ether segment grafted aramid is as shown in Formula 2, x=1; R1 is isophthalic acid R2 is -CH3, m+n=146.
[0081] The method for preparing an aramid-based solid polymer electrolyte membrane having hydrogen bond defects comprises the following steps:
[0082] (1) adding ether segment grafted aramid and NaFSI in a mass ratio of 1:4 (NaFSI accounts for 80% of the total mass) into DMF solvent, stirring until fully dispersed and dissolved to form a homogeneous precursor solution, standing to degas, and forming a casting film precursor solution;
[0083] (2) The casting precursor liquid is uniformly coated on the surface of the glass plate to form a film, and first evaporated and dried at a temperature of 60°C for 15 hours; then transferred to a high temperature vacuum oven at a temperature of 90°C for baking and drying to obtain a conductive solid polymer electrolyte membrane.
[0084] Aramid-based solid polymer electrolyte membrane with hydrogen bond defects 3#
[0085] The aramid-based solid polymer electrolyte membrane 3# with hydrogen bond defects is composed of two substances: chemically modified ether segment grafted aramid with hydrogen bond defects and sodium bis(fluorosulfonyl)imide (NaFSI).
[0086] The preparation method of chemically modified ether segment grafted aramid with hydrogen bond defects comprises the following steps:
[0087] S1: dissolving poly(m-phenylene isophthalamide) and 1-bromo-3,6,9,12-tetraoxatridecane in a polar solvent DMF, adding an acid-binding agent potassium hydroxide, and reacting at a temperature of 50° C. to obtain an intermediate product;
[0088] S2: adding hydrochloric acid solution to the intermediate product obtained in step S1 for precipitation, and then washing and drying in sequence to obtain ether segment grafted aramid, wherein the structure of the ether segment grafted aramid is as shown in Formula 1, x=4; R1 is isophthalic acid R2 is -CH3, m+n=146.
[0089] The method for preparing an aramid-based solid polymer electrolyte membrane having hydrogen bond defects comprises the following steps:
[0090] (1) adding ether segment grafted aramid and NaFSI in a mass ratio of 1:3 (NaFSI accounts for 75% of the total mass) into DMF solvent, stirring until fully dispersed and dissolved to form a homogeneous precursor solution, standing to degas, and forming a casting film precursor solution;
[0091] (2) The casting precursor liquid is uniformly coated on the surface of the glass plate to form a film, and first evaporated and dried at a temperature of 45°C for 10 hours; then transferred to a high-temperature vacuum oven at a temperature of 80°C for baking and drying, thereby obtaining an aramid-based solid polymer electrolyte membrane with hydrogen bond defects.
[0092] Aramid-based solid polymer electrolyte membrane with hydrogen bond defects 4#
[0093] Based on the aramid solid electrolyte membrane 2# with hydrogen bond defects, the main difference is that the aramid-based solid polymer electrolyte membrane 4# with hydrogen bond defects is based on the aramid solid electrolyte membrane 2# with hydrogen bond defects and a small molecule ion transporter is added. It is composed of three substances: chemically modified ether segment grafted aramid with hydrogen bond defects, sodium bis(fluorosulfonyl)imide (NaFSI) and diethylene glycol dimethyl ether (G2).
[0094] The method for preparing an aramid-based solid polymer electrolyte membrane having hydrogen bond defects comprises the following steps:
[0095] (1) adding ether segment grafted aramid and NaFSI in a mass ratio of 1:4 (NaFSI accounts for 80% of the total mass) into DMF solvent, stirring until fully dispersed and dissolved to form a homogeneous precursor solution, standing to degas, and forming a casting film precursor solution;
[0096] (2) The casting precursor liquid is uniformly coated on the surface of the glass plate to form a film, and first evaporated and dried at a temperature of 55°C for 10 hours; then the temperature is transferred to a high-temperature vacuum oven at 90°C for baking and drying, thereby obtaining an aramid-based solid polymer electrolyte membrane 2# with hydrogen bond defects.
[0097] (3) According to the mass ratio, 10% of diethylene glycol dimethyl ether (G2) small molecule ion transporter was added to the aramid-based solid polymer electrolyte membrane 2# with hydrogen bond defects under dry conditions to prepare the aramid-based solid polymer electrolyte membrane 4# with hydrogen bond defects.
[0098] Aramid-based solid polymer electrolyte membrane with hydrogen bond defects 5#
[0099] Based on the aramid solid electrolyte membrane 2# with hydrogen bond defects, the main difference is that the aramid-based solid polymer electrolyte membrane 5# with hydrogen bond defects is based on the aramid solid electrolyte membrane 2# with hydrogen bond defects and inorganic ceramic particle fillers are added, which is composed of ether segment grafted aramid and sodium bis(fluorosulfonyl)imide (NaFSI) and Na3Zr2Si2PO 12 It is composed of three substances.
[0100] The method for preparing an aramid-based solid polymer electrolyte membrane having hydrogen bond defects comprises the following steps:
[0101] (1) The ether chain segments were grafted onto aramid and NaFSI in a mass ratio of 1:4 (NaFSI accounted for 80% of the total mass of the two) and Na3Zr2Si2PO 12 (accounting for 5% of the total mass) was added into the DMF solvent, stirred until fully dispersed and dissolved to form a homogeneous precursor solution, and allowed to stand for degassing to form a casting film precursor solution;
[0102] (2) The casting precursor liquid is uniformly coated on the surface of the glass plate to form a film, and first evaporated and dried at a temperature of 55°C for 10 hours; then transferred to a high temperature vacuum oven at a temperature of 90°C for baking and drying, to obtain an aramid-based solid polymer electrolyte membrane 5# with hydrogen bond defects.
[0103] Aramid-based solid polymer electrolyte membrane with hydrogen bond defects 6#
[0104] The aramid-based solid polymer electrolyte membrane 6# with hydrogen bond defects is composed of two substances: chemically modified ether segment grafted aramid with hydrogen bond defects and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0105] The preparation method of chemically modified ether segment grafted aramid with hydrogen bond defects comprises the following steps:
[0106] S1: dissolving poly(p-phenylene terephthalamide) and 2-bromoethyl methyl ether in a polar solvent DMF, adding an acid-binding agent sodium hydride, and reacting at a temperature of 50° C. to obtain an intermediate product;
[0107] S2: adding water to the intermediate product obtained in step S1 to precipitate, and then washing and drying in sequence to obtain ether segment grafted aramid, wherein the structure of the ether segment grafted aramid is as shown in Formula 1, x=1; R1 is benzene R2 is -CH3, m+n=146.
[0108] The method for preparing an aramid-based solid polymer electrolyte membrane having hydrogen bond defects comprises the following steps:
[0109] (1) adding chemically modified ether chain segment grafted aramid with hydrogen bond defects and LiTFSI in a mass ratio of 1:2 (LiTFSI accounts for 67% of the total mass) into DMF solvent, stirring until fully dispersed and dissolved to form a homogeneous precursor solution, standing to degas, and forming a casting film precursor solution;
[0110] (2) The casting precursor liquid is uniformly coated on the surface of the glass plate to form a film, and first evaporated and dried at a temperature of 55°C for 10 hours; then transferred to a high-temperature vacuum oven at a temperature of 90°C for baking and drying, to obtain an aramid-based solid polymer electrolyte membrane with hydrogen bond defects.
[0111] Aramid-based solid polymer electrolyte membrane with hydrogen bond defects 7#
[0112] The aramid-based solid polymer electrolyte membrane 7# with hydrogen bond defects is composed of two substances: chemically modified ether segment grafted aramid with hydrogen bond defects and potassium tetrachloroaluminate (KAlCl4).
[0113] The preparation method of chemically modified ether segment grafted aramid with hydrogen bond defects comprises the following steps:
[0114] S1: dissolving poly(p-phenylene terephthalamide) and 2-(2-ethoxyethoxy)ethyl bromide in a polar solvent DMF, adding an acid-binding agent sodium hydride, and reacting at a temperature of 50° C. to obtain an intermediate product;
[0115] S2: adding water to the intermediate product obtained in step S1 to carry out precipitation reaction, and then washing and drying in sequence to obtain ether segment grafted aramid, wherein the structure of the ether segment grafted aramid is as shown in Formula 1, x=2; R1 is benzene R2 is -C2H5, m+n=146.
[0116] The method for preparing an aramid-based solid polymer electrolyte membrane having hydrogen bond defects comprises the following steps:
[0117] (1) adding chemically modified ether segment grafted aramid with hydrogen bond defects and KAlCl4 in a mass ratio of 1:4 (KAlCl4 accounts for 80% of the total mass) into DMF solvent, stirring until fully dispersed and dissolved to form a homogeneous precursor solution, standing for degassing, and forming a film casting precursor solution;
[0118] (2) The casting precursor liquid is uniformly coated on the surface of the glass plate to form a film, and first evaporated and dried at a temperature of 55°C for 10 hours; then transferred to a high temperature vacuum oven at a temperature of 90°C for baking and drying, thereby obtaining an aramid-based solid polymer electrolyte membrane with hydrogen bond defects.
[0119] The conductivity of the aramid-based solid polymer electrolyte membrane with hydrogen bond defects prepared above was tested, and the results are shown in Table 1.
[0120] Table 1
[0121]
[0122]
[0123] Referring to Table 1, it can be seen that the conductivity of the aramid-based solid polymer electrolyte membrane with hydrogen bond defects at 40°C is not less than 10 -8 S / cm, conductivity at 80℃ not less than 10 -6 S / cm. The mass loss at 200°C does not exceed 13%. The aramid-based solid polymer electrolyte membrane with hydrogen bond defects in the present application can form a typical flexible polymer membrane with self-supporting ability, has the ability to be compatible with lithium, sodium, and potassium metal salts, and exhibits certain ion conductivity.
[0124] refer to Figure 1 As shown, Figure 1 The NMR spectrum of the aramid matrix grafted with ether segments having hydrogen bond defects in the aramid-based solid polymer electrolyte membrane 1# having hydrogen bond defects is shown.
[0125] refer to Figure 2 , Figure 3 As shown, Figure 2 A physical picture of an aramid-based solid polymer electrolyte membrane 1# having hydrogen bonding defects is shown. Figure 3 The actual image of aramid-based solid polymer electrolyte membrane 2# with hydrogen bond defects is shown. It can be seen that the ether segment grafted aramid and the metal salt have good compatibility after mixing, and become a uniform and transparent state. The aramid-based solid polymer electrolyte membrane shows complete self-supporting ability and objective mechanical modulus.
[0126] refer to Figure 4 ,5 As shown, Figure 4 , 5 The electrochemical impedance spectroscopy of aramid-based solid polymer electrolyte membranes 1# and 2# with hydrogen bond defects at 40°C and 80°C are shown respectively. It can be seen that at 9% salt content, the conductivity of the solid polymer electrolyte membrane is 10 -8 S / cm; when the salt content increases to 80%, its conductivity increases to nearly 10 -6 S / cm, and its conductivity increased by nearly two orders of magnitude, proving that salt concentration has an important influence on sodium ion transport. At ultra-high concentrations, the enhanced sodium ion transport capacity is due to the perturbation effect of the grafted structure of aramid, which can induce the formation of a conductive network with a weak coordination structure at high salt concentrations, forming a localized ion transport path. At 80°C, the conductivity of the electrolyte membrane with a salt content of 80% exceeds 10 -4 S / cm, and has excellent mechanical properties. This conductivity is greatly improved compared to traditional all-solid polymer electrolytes with similar rigid structures, proving the potential of aramid-based solid polymer electrolyte membranes with hydrogen bond defects in aramid-based sodium ions grafted onto ether segments. Figure 6 As shown, Figure 6 The electrochemical impedance spectroscopy of aramid-based solid polymer electrolyte membrane 3# with hydrogen bond defects at 40°C and 80°C is shown. It can be seen that optimizing the length of the ether segment can improve the ion transport capacity of the solid polymer electrolyte membrane to a certain extent. Figure 7 , 8 As shown, Figure 7 , 8 The electrochemical impedance spectroscopy of aramid-based solid polymer electrolyte membranes 4# and 5# with hydrogen bond defects at 40°C and 80°C are shown respectively. It can be seen that both small molecule ion transport agents and inorganic ceramic fillers can significantly improve the ion transport capacity of solid polymer electrolyte membranes while maintaining the solid structural characteristics of polymer electrolytes, reaching 10 -4 S / cm level fully meets the use requirements. Fig. 9 , 10 As shown, Fig. 9 , 10 The electrochemical AC impedance diagrams of aramid-based solid polymer electrolyte membranes 6# and 7# with hydrogen bond defects at 40°C and 80°C are shown respectively, indicating that in addition to sodium ions, the aramid-based solid polymer electrolyte membrane with hydrogen bond defects of the present invention also has the ability to transport lithium and potassium metals, which is conducive to expanding the application scope of the aramid-based solid polymer electrolyte membrane with hydrogen bond defects of the present invention.
[0127] Example 2
[0128] Battery 1#
[0129] The prepared aramid-based solid polymer electrolyte membrane 2# with hydrogen bond defects was assembled with two circular sodium sheet electrodes with a thickness of 300 um and a diameter of 12 mm to form a sodium / sodium symmetric battery, that is, the aramid-based solid polymer electrolyte membrane with hydrogen bond defects was placed in the middle and the sodium electrodes were located on both sides to form a sandwich structure, which was then loaded into a button battery mold shell and pressed into a battery.
[0130] Battery 2#
[0131] The prepared aramid-based solid polymer electrolyte membrane 3# with hydrogen bond defects was assembled with two circular lithium sheet electrodes with a thickness of 300 um and a diameter of 12 mm to form a lithium / lithium symmetrical battery, that is, the aramid-based solid polymer electrolyte membrane with hydrogen bond defects was placed in the middle, and the lithium electrodes were located on both sides to form a sandwich structure, which was then loaded into a button battery mold shell and pressed into a battery.
[0132] Battery 3#
[0133] Hard carbon, conductive carbon black (Super-P) and binder sodium carboxymethyl cellulose (CMC) / styrene-butadiene rubber (SBR) were mixed in a mass ratio of 8:1:1 and coated on the surface of the metal aluminum current collector, punched into a circular sheet with a diameter of 14 mm, and dried in a vacuum to obtain a negative electrode sheet.
[0134] The oxide-containing positive electrode (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2), conductive agent Super-P and binder polyvinylidene fluoride are mixed in a mass ratio of 8:1:1 and coated on the surface of the metal aluminum current collector, punched into a circular sheet with a diameter of 12 mm, and dried in a vacuum to obtain a positive electrode sheet.
[0135] The above-mentioned negative electrode sheet, positive electrode sheet and aramid-based solid polymer electrolyte membrane 5# with hydrogen bond defects are formed into a sandwich structure, which is then loaded into a battery mold shell and pressed into a hard carbon / NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 full battery.
[0136] Battery 4#
[0137] Hard carbon, conductive carbon black (Super-P) and binder sodium carboxymethyl cellulose (CMC) / styrene-butadiene rubber (SBR) were mixed in a mass ratio of 8:1:1 and coated on the surface of the metal aluminum current collector, punched into a circular sheet with a diameter of 14 mm, and dried in a vacuum to obtain a negative electrode sheet.
[0138] A polyanionic sodium iron pyrophosphate positive electrode (NaFeP2O7), a conductive agent Super-P and a binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1 and coated on the surface of a metal aluminum current collector, punched into a circular sheet with a diameter of 12 mm, and dried in a vacuum to obtain a positive electrode sheet.
[0139] The above-mentioned negative electrode sheet, positive electrode sheet and aramid-based solid polymer electrolyte membrane 6# with hydrogen bond defects are formed into a sandwich structure, which is then loaded into a battery mold shell and pressed into a hard carbon / NaFeP2O7 full battery.
[0140] Battery 5#
[0141] Graphite, conductive carbon black (Super-P) and binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1 and coated on the surface of the metal aluminum current collector, punched into a circular sheet with a diameter of 14 mm, and dried in a vacuum to obtain a negative electrode sheet.
[0142] A positive electrode containing Prussian blue, a conductive agent Super-P and a binder polyvinylidene fluoride were mixed in a mass ratio of 8:1:1 and coated on the surface of a metal aluminum current collector, punched into a circular sheet with a diameter of 12 mm, and dried in a vacuum to obtain a positive electrode sheet.
[0143] The negative electrode sheet, the positive electrode sheet and the aramid-based solid polymer electrolyte membrane 4# with hydrogen bond defects are formed into a sandwich structure, which is then loaded into a battery mold shell and pressed into a graphite / Prussian blue full battery.
[0144] The electrochemical performance of the battery prepared above was tested, and the results are shown in Table 2.
[0145] Table 2
[0146]
[0147] Refer to Table 2 and Figure 11-15 As shown, it can be seen that the lithium, sodium, and potassium batteries of different forms prepared by the present invention can all achieve reversible charge and discharge cycles, thanks to the good ion transport capability and excellent chemical and electrochemical stability of the aramid-based solid polymer electrolyte membrane with hydrogen bond defects, which can not only transport a variety of metal ions, but also show greater compatibility with a variety of positive and negative electrode materials. The different battery application tests of Example 2 further prove that the aramid-based solid polymer electrolyte membrane with hydrogen bond defects has the initial value of developing high-safety solid-state batteries.
[0148] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. An aramid-based solid polymer electrolyte membrane having hydrogen bond defects, characterized in that: The aramid-based solid polymer electrolyte membrane with hydrogen bond defects comprises a chemically modified ether segment grafted aramid matrix and an anhydrous alkali metal salt; The chemically modified ether chain segment grafted aramid matrix is obtained by grafting ether chains on the para-position or meta-position aramid NH sites.
2. The aramid-based solid polymer electrolyte membrane with hydrogen bonding defects according to claim 1, characterized in that: The structural formula of chemically modified ether segment grafted aramid is as follows: Wherein, in Formula 1 and Formula 2, m+n is selected from an integer of 10-10000 and satisfies 0.2≤m / (m+n)≤1; r represents a random copolymer; R1 represents a phenyl group or m-phenyl x is an integer selected from 1-5; R2 is -C y H 2y+1 or -C y H z F 2y+1-z , y is an integer selected from 1-4, and z is an integer satisfying 0≤z≤2y+1.
3. The aramid-based solid polymer electrolyte membrane with hydrogen bonding defects according to claim 1, characterized in that: The preparation method of chemically modified ether segment grafted aramid fiber comprises the following steps: S1: dissolving a certain amount of aramid and halogenated ether monomer in a polar solvent, adding an acid binding agent, and reacting at a temperature of 50-80°C to obtain an intermediate product; S2: adding a precipitant to the intermediate product obtained in step S1 to react, and then washing and drying in sequence to obtain chemically modified ether segment grafted aramid.
4. The aramid-based solid polymer electrolyte membrane with hydrogen bonding defects according to claim 3, characterized in that: The halogenated ether is one of chloroether, bromoether or iodoether; and / or the aramid is one of poly(p-phenylene terephthalamide) or poly(m-phenylene isophthalamide); and / or the acid binding agent is one or more of potassium hydroxide, sodium hydroxide, potassium carbonate or sodium hydride; and / or the precipitant is one or more of water, hydrochloric acid solution, methanol, ethanol, and sodium chloride solution; And / or the polar solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
5. The aramid-based solid polymer electrolyte membrane with hydrogen bonding defects according to claim 1, characterized in that: The anhydrous alkali metal salt is a lithium salt, a sodium salt or a potassium salt; Further, the lithium salt is one or more of lithium chloride, lithium bromide, lithium iodide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium trifluoroacetate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, lithium bis(fluorooxalatoborate), lithium tetrachloroaluminate, and polymer lithium salts; The sodium salt is one or more of sodium chloride, sodium bromide, sodium iodide, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate, sodium hexafluoroarsenate, sodium trifluoroacetate, sodium trifluoromethanesulfonate, sodium bis(trifluoromethanesulfonyl)imide, sodium bis(pentafluoroethanesulfonyl)imide, sodium bis(fluorooxalatoborate), sodium tetrachloroaluminate, and polymer sodium salt; The potassium salt is one or more of potassium chloride, potassium bromide, potassium iodide, potassium hexafluorophosphate, potassium tetrafluoroborate, potassium perchlorate, potassium hexafluoroarsenate, potassium trifluoroacetate, potassium trifluoromethanesulfonate, potassium bisfluorosulfonyl imide, potassium bis(trifluoromethanesulfonyl)imide, potassium bis(pentafluoroethanesulfonyl)imide, potassium bisfluorooxalatoborate, potassium tetrachloroaluminate, and polymer potassium salt.
6. The aramid-based solid polymer electrolyte membrane with hydrogen bonding defects according to claim 1, characterized in that: It also includes an ion conduction auxiliary agent; the ion conduction auxiliary agent is a small molecule ion transport agent and / or oxides, sulfides, halides and inorganic particles or salt fillers thereof.
7. The aramid-based solid polymer electrolyte membrane with hydrogen bonding defects according to claim 6, characterized in that: The small molecule ion transporter is one or more of cyclic carbon (sulfonate) esters, chain carbon (sulfonate) esters, cyclic ethers, chain ethers, sulfones, nitriles, and phosphates.
8. The aramid-based solid polymer electrolyte membrane with hydrogen bonding defects according to claim 6, characterized in that: Oxides, sulfides, halides and their inorganic particles or salt fillers are SiO2, TiO2, Al2O3, Li 3.3 La 0.56 TiO3, LiTi2(PO4)3, Li 14 Zn(GeO4), Li7La3Zr2O 12 , Li2S-P2S5, LiBH4, LiF, LiI, LiCl, LiAlCl4, Li3OCl, LiPON, Na3Zr2Si2PO 12 、Na3PS4、Na3SbS4、Na 11 Sn2PS 12 、Na4Sn 0.67 Si 0.33 One or more of S4, NaF, NaI, NaCl, NaAlCl4, KF, KI, KCl, KAlCl4, AlCl3.
9. A method for preparing an aramid-based solid polymer electrolyte membrane having hydrogen bonding defects according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) adding a raw material chemically modified ether chain segment grafted aramid matrix and anhydrous alkali metal salt into a solvent in a certain proportion to form a film casting precursor solution; (2) The casting precursor liquid is uniformly applied to the surface of the glass plate to form a film, and firstly dried at a temperature of 25-60° C.; and then dried at a temperature of 60-90° C. in a second step to obtain an aramid-based solid polymer electrolyte membrane with hydrogen bond defects.
10. A battery, characterized in that: The battery is one of a lithium battery, a sodium battery or a potassium battery, and comprises an electrolyte, a negative electrode and a positive electrode to form a sandwich structure, and the aramid-based solid polymer electrolyte membrane with hydrogen bond defects as claimed in claim 1 is contained between the positive electrode and the negative electrode.